Cane cutters and their understanding about social and environmental training - Franzi, Simone [UNESP]; Spazziani, Maria de Lourdes [UNESP] (Univ Metodista Piracicaba-unimep, 2015)
This study aims to identify and analyze the insights of cutting workers of cane sugar entered in the Youth and Adult Education, about school contributions in environmental training. Understanding how important is knowledge of relevant issues in this field we used a theoretical framework that will address the reality of cane cutters, who seek education as a means of better living conditions, and the importance of Environmental Education in this training process, counting on the contributions of Freire's perspective. We believe in the potential of this aspect for its viability to reflect on the relationship between oppressor and oppressed against a liberating education. From the qualitative research, we found methodological elements in oral history as a way to listen and talk to the interviewees. Given the purpose of the study, nine narratives were collected. They indicate that although the cane cutters understand the education as an important factor, their understanding about the natural and social environment do not seem to suffer any impact to consolidate a broader and more critical formation.
Keywords: SOCIAL AND ENVIRONMENTAL ASPECTS; SCHOOL EDUCATION; CUTTER CANE